Phase portraits of the quadratic polynomial Liénard differential systems - Gouveia, Márcio R. A. [UNESP] (2020)
We classify the global phase portraits in the Poincaré disc of the quadratic polynomial Liénard differential systems where (x, y) ϵR 2 are the variables and a,b,c,d,e are real parameters.